2017
DOI: 10.1111/jog.13370
|View full text |Cite
|
Sign up to set email alerts
|

Number of parity and the risk of rheumatoid arthritis in women: A dose–response meta‐analysis of observational studies

Abstract: Aim: The association between parity and rheumatoid arthritis (RA) risk has been investigated, but results are controversial. Thus, our aim was to systematically analyze the effect of number of parity on the risk of RA in women. Methods: Relevant published studies were identified using PUBMED and EMBASE databases through 1 April 2016. We pooled the relative risks (RR) and 95% confidence intervals (CI) using random-effects models. Results: In all, 12 studies with a total of 2 497 580 participants and 11 521 RA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…As discussed in our introduction, Ren et al have previously systematically reviewed the relationship between parity and the risk of RA in women (19). Our systematic review builds on their earlier work, by evaluating the association between both parity and gravidity and the risk of RA, examining the impact of serology on RA risk, and assessing if risk differs during pregnancy, and the post-partum period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in our introduction, Ren et al have previously systematically reviewed the relationship between parity and the risk of RA in women (19). Our systematic review builds on their earlier work, by evaluating the association between both parity and gravidity and the risk of RA, examining the impact of serology on RA risk, and assessing if risk differs during pregnancy, and the post-partum period.…”
Section: Discussionmentioning
confidence: 99%
“…The "protective effect" of previous pregnancy and childbirth has not, however, been replicated across all studies (16)(17)(18), and its precise impact on RA susceptibility remains uncertain. To date, one systematic literature review and meta-analysis has been undertaken in this area, reporting an inverse relationship between parity and RA risk (19). This review did not, however, evaluate risk by gravidity or childbirth timing, and included results from different analyses undertaken in the same patient groups (including two publications from the Nurses' Health Study, and two from a case-control population in Seattle, USA) (16,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…>7 years) (119121). Less clear is the relationship between parity and risk for RA, with one study showing no increased risk for seropositive RA based on one or more pregnancies (122), and other studies including a meta-analysis demonstrating a protective effect of pregnancies (123, 124). …”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%
“…with RA include age at menarche 7,8 , age at menopause [9][10][11][12] , parity [13][14][15][16][17][18] , breast feeding 8,[19][20][21][22] , use of oral contraceptives (OC) [23][24][25][26][27][28] , and hormonal replacement therapy (HRT) 29,30 . For the development of RA, these factors have been described as protective factors 8,14,18,[20][21][22]24,[27][28][29] , risk factors 9,10,12,15,17,23 , or irrelevant 11,25,26,30 , depending on the study, leading to inconsistent results. Previous literature showed that the effect of parity on RA varies with age 15,18 .…”
mentioning
confidence: 99%